Pengujian Kekerasan Dan Struktur Mikro Plat Baja Karbon Rendah Setelah Proses Pemanasan Dengan Suhu 8000c Di Quenching Bio Solar - AHMADIN AHMADIN (UNIVERSITAS PROF. DR. HAZAIRIN, SH BENGKULU, 2021)
Hardness is one of the mechanical properties in material. One of the process that influence hardness is heat treatment that is given heat with temperature 800 0C. The cooling sistem are non treatmen and quenching that it use air, water, biosolar. The result from this research are 0,306 BHN of the non treatment and quenching method 44,243BHN (cooling in the air), 882,143 BHN (cooling in the water) and 49,349BHN (cooling in the Biosolar).Microstructure is details of a metal object that are very small and invisible to see with naked eyes. Because of that condition it use optic microscope and electron microscope to check details of the steels. The result of this process are non treatment (26,4 ?m) and quenching process air (21,7 ?m), water (22,6 ?m) and Biosolar (22,7 ?m). Phase that happen are ferrite and pearlite in the iron, low carbon steel.Keywords: Hardness test, micro